2018
DOI: 10.1021/acs.analchem.8b02486
|View full text |Cite
|
Sign up to set email alerts
|

Screening Estrogen Receptor Modulators in a Paper-Based Breast Cancer Model

Abstract: The health risks associated with acute and prolonged exposure to estrogen receptor (ER) modulators has led to a concerted effort to identify and prioritize potential disruptors present in the environment. ER agonists and antagonists are identified with end-point assays, quantifying changes in cellular proliferation or gene transactivation in monolayers of estrogen receptor alpha expressing (ER+) cells upon exposure. While these monolayer cultures can be prepared, dosed, and analyzed in a highly parallelized ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 52 publications
(106 reference statements)
0
22
0
Order By: Relevance
“…We recently showed that 96-zone paper scaffolds could be loaded consistently with a multichannel pipette with RSD values of 10.6%–21.4% across a single deposition; 8.6%–19.9% across multiple depositions with the same pipette tip, and; 15.1% across an entire plate. 30 While reproducible seeding is user dependent and improves with practice, inconsistencies in cell density can be eliminated with the incorporation of liquid handlers capable of accurately and reproducibly seeding each zone.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that 96-zone paper scaffolds could be loaded consistently with a multichannel pipette with RSD values of 10.6%–21.4% across a single deposition; 8.6%–19.9% across multiple depositions with the same pipette tip, and; 15.1% across an entire plate. 30 While reproducible seeding is user dependent and improves with practice, inconsistencies in cell density can be eliminated with the incorporation of liquid handlers capable of accurately and reproducibly seeding each zone.…”
Section: Resultsmentioning
confidence: 99%
“…Acrylic and food-grade silicone are biocompatible and have been used to prepare microfabricated devices for cell culture previously. [29][30][31] To ensure the laser-cut components † Electronic supplementary information (ESI) available. See DOI: 10.1039/c9ay01690b could support prolonged cell culture, we incubated them in contact with parental M231 cells suspended in Matrigel at a final density of 2000 cells per μL.…”
Section: Bloccs Are Compatible With Prolonged Cell Culturementioning
confidence: 99%
“…Owing to its significant advantages such as low-cost, easy fabrication and disposal, flexibility and renewability, paper has played a very important role in the propagation and development of human civilization since ancient times. Various types of paper with different physical and chemical properties were created in the past thousands of years, making a huge library of substrate materials for both industry production and scientific research. The easy deformation properties (by cutting or folding) of the paper have also led to various innovative technologies and applications. Because of these superiorities, paper has been widely applied in publications, packages, point-of-care test (POCT) devices, filters, and so forth, in every corner of our daily life. It has also been frequently employed in scientific research, as substrate materials to grow nanomaterials, perform bioanalysis, , culture cells, and fabricate various paper-based devices. …”
Section: Introductionmentioning
confidence: 99%
“…In many applications, paper has to be functionalized to alter its physical/chemical properties or bioactivities, for example, hydrophilicity, reactivity, biocompatibility, antifouling and antibacterial performances. , Patterning of physical and chemical properties on paper is also commonly required in the fabrication of paper-based microarrays and microfluidics, which are widely used in cell incubation devices, POCT settings, , and paper-based electronic devices. , Many techniques have been used to functionalize paper and create patterns. Chemical functionalization on pure cellulose paper could easily be achieved because of the existence of numerous hydroxyl groups on cellulose molecules, which can react with various functional groups, allowing the covalent attachment of designed molecules on the paper substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation